In-host adaptation and acquired triazole resistance in Aspergillus fumigatus: a dilemma for clinical management. Issue 11 (November 2016) - Verweij, Paul E; Zhang, Jianhua; Debets, Alfons J M; Meis, Jacques F; van de Veerdonk, Frank L; Schoustra, Sijmen E; Zwaan, Bas J; Melchers, Willem J G
Summary: Aspergillus fumigatus causes a range of diseases in human beings, some of which are characterised by fungal persistence. A fumigatus can persist by adapting to the human lung environment through physiological and genomic changes. The physiological changes are based on the large biochemical versatility of the fungus, and the genomic changes are based on the capacity of the fungus to generate genetic diversity by spontaneous mutations or recombination and subsequent selection of the genotypes that are most adapted to the new environment. In this Review, we explore the adaptation strategies of A fumigatus in relation to azole resistance selection and the clinical implications thereof for management of diseases caused by Aspergillus spp. We hypothesise that the current diagnostic tools and treatment strategies do not take into account the biology of the fungus and might result in an increased likelihood of fungal persistence in patients. Stress factors, such as triazole exposure, cause mutations that render resistance. The process of reproduction—ie, sexual, parasexual, or asexual—is probably crucial for the adaptive potential of Aspergillus spp. As any change in the environment can provoke adaptation, switching between triazoles in patients with chronic pulmonary aspergillosis might result in a high-level pan-triazole-resistant phenotype through the accumulation of resistance mutations. Alternatively, when triazole therapy is stopped, an azole-free environment is created that could prompt selection for compensatory mutations that overcome any fitness costs that are expected to accompany resistance development. As a consequence, starting, switching, and stopping azole therapy has the risk of selecting for highly resistant strains with wildtype fitness. A similar adaptation is expected to occur in response to other stress factors, such as endogenous antimicrobial peptides; over time the fungus will become increasingly adapted to the lung environment, thereby limiting the probability of eradication. Our hypothesis challenges current management strategies, and future research should investigate the genomic dynamics during infection to understand the key factors facilitating adaptation of Aspergillus spp.